Multi‐Dimensional Printing for Bone Tissue Engineering. Issue 11 (19th April 2021) - Qu, Moyuan; Wang, Canran; Zhou, Xingwu; Libanori, Alberto; Jiang, Xing; Xu, Weizhe; Zhu, Songsong; Chen, Qianming; Sun, Wujin; Khademhosseini, Ali
Abstract: The development of 3D printing has significantly advanced the field of bone tissue engineering by enabling the fabrication of scaffolds that faithfully recapitulate desired mechanical properties and architectures. In addition, computer‐based manufacturing relying on patient‐derived medical images permits the fabrication of customized modules in a patient‐specific manner. In addition to conventional 3D fabrication, progress in materials engineering has led to the development of 4D printing, allowing time‐sensitive interventions such as programed therapeutics delivery and modulable mechanical features. Therapeutic interventions established via multi‐dimensional engineering are expected to enhance the development of personalized treatment in various fields, including bone tissue regeneration. Here, recent studies utilizing 3D printed systems for bone tissue regeneration are summarized and advances in 4D printed systems are highlighted. Challenges and perspectives for the future development of multi‐dimensional printed systems toward personalized bone regeneration are also discussed. Abstract : In the past decade, the development of multi‐dimensional printing has significantly advanced the field of bone tissue engineering by fabricating scaffolds with biomimetic mechanical properties, architectures, and programmable drug release profiles. This review focuses on summarizing recent advances in 3D printed scaffolds, 3D printed drug delivery systems (DDS), and 4D printing strategies for accelerated bone tissue regeneration.